a) 3x - 8 = 2x + 4 b) 5x - 3 = 4x + 6 c) 7x – 9 = 6x - 8 d) 7x - 5 = 6x + 8 e) 5x - 8 = 4x + 9 f) 9x - 4= 8x + 5 g) 12x + 4 = 11x + 15 h) 3x - 1 = 2x + 1 i) 2x + 7 = x - 1​



Odpowiedź :

Odpowiedź:

a)

3x - 8 = 2x + 4

3x - 2x = 4 + 8

x = 12

b)

5x - 3 = 4x + 6

5x - 4x = 6 + 3

x = 9

c)

7x – 9 = 6x - 8

7x - 6x = -8 + 9

x = 1

d)

7x - 5 = 6x + 8

7x - 6x = 8 + 5

x = 13

e)

5x - 8 = 4x + 9

f)

9x - 4= 8x + 5

9x - 8x = 5 + 4

x = 9

g)

12x + 4 = 11x + 15

h)

3x - 1 = 2x + 1

3x - 2x = 1 + 1

x = 2

i)

2x + 7 = x - 1​

2x - x = -1 - 7

x = -8

Szczegółowe wyjaśnienie:

Odpowiedź:

A. 3x-8=2x+4

x=12

B.5x-3=4x+6

x=9

C.7x-9=6x-8

x=1

D.7x-5=6x+8

x=13

E. 5x-8=4x+9

x=17

F. 9x-4=8x+5

x=9

G. 12x+4=11x+15

x=11

H.3x-1=2x+1

x=2

I. 2x+7=x-1

x= -8

Wyjaśnienie:

Trzeba przerzucić x na lewo,a liczby na prawo wraz ze zmianą znaków.

Przykład:

2x-5=2+x

2x-x=2+5

x=7

Mam nadzieję,że pomogłam <3

Inne Pytanie